2014
DOI: 10.1111/are.12396
|View full text |Cite
|
Sign up to set email alerts
|

Sperm cryopreservation of silver barb (Barbodes gonionotus): cryoprotectants, cooling rate and storage time on sperm quality

Abstract: Effectiveness and efficiency of frozen sperm on fertilization and hatching success of eggs from silver barb was examined in relation to cryoprotectants, freezing rate and storage period. Sperm was diluted in calcium-free Hank's balanced salt solution, equilibrated with dimethylsulphoxide (DMSO), propylene glycol, sucrose or methanol at 5%, 10%, 15% or 20% final concentrations, and frozen in 250-lL straws using a one-step freezing procedure (1, 5 and 8°C min À1 from 25 to À40°C). Highest post-thaw sperm motilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Afterwards, percentages of forward‐moving sperm from each male were separately evaluated based on subjective estimation following protocol of Vuthiphandchai et al . (). Briefly, semen from each male was placed on a microscopic slide, activated with distilled water (100 μL) and observed at 40× magnification using a light microscope (Zeiss model D‐7085; Berlin, Germany).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Afterwards, percentages of forward‐moving sperm from each male were separately evaluated based on subjective estimation following protocol of Vuthiphandchai et al . (). Briefly, semen from each male was placed on a microscopic slide, activated with distilled water (100 μL) and observed at 40× magnification using a light microscope (Zeiss model D‐7085; Berlin, Germany).…”
Section: Methodsmentioning
confidence: 97%
“…Silver barb, Barbodes gonionotus , is recognized as one of economically important freshwater fish of Thailand. Recently, cryopreservation of silver barb sperm was carried out by Vuthiphandchai, Wilairattanadilok, Chomphuthawach, Sooksawat and Nimrat () who focused on the effects of cryoprotectants, cooling rate and storage time on post‐thawed sperm quality.…”
Section: Introductionmentioning
confidence: 99%
“…Sperm motility was assessed from the forward movement, while vibrating spermatozoa were judged as immotile sperm. Percentage of forward‐moving sperm was expressed based on quantitative motility score from immotile (0%) and every 20% increment in a forward direction until reaching a maximum score (100%) that referred to highly active motile sperm (Vuthiphandchai et al., ). Evaluation of sperm motility was done within 15s post‐activation and by the same experienced personnel to eliminate the degree of variation among observers.…”
Section: Methodsmentioning
confidence: 99%
“…Calcium‐free Hank's balanced salt solution (Ca‐F HBSS) was used to dilute pooled semen (Vuthiphandchai et al., ). The extender comprised (g L −1 ) NaCl (8.89), KCl (0.44), Na 2 HPO 4 ·2H 2 O (0.13), NaHCO 3 (0.39), KH 2 PO 4 (0.07), MgSO 4 ·7H 2 O (0.22) and glucose (1.11).…”
Section: Methodsmentioning
confidence: 99%
“…Silver barb, Barbodes gonionotus , is widely cultured as an economically important freshwater fish species in Southeast Asian countries, especially in Thailand. Several authors have reported successful cryopreservation protocols of silver barb sperm using a programmable controlled freezer (Routray et al, ; Sarder, Rahman, Hossain, & Samad, ; Vuthiphandchai, Wilairattanadilok, Chomphuthawach, Sooksawat, & Nimrat, ).…”
Section: Introductionmentioning
confidence: 99%